Synthesis of silica xeorogel@Mg-Al layered double hydroxide composite for CO2 capture - Eren, Dicle; Sari Yilmaz, Muge (YILDIZ TECHNICAL UNIV, 2024)
Today, the increase in the level of carbon dioxide (CO2) gas in the atmosphere has started to cause concern. Therefore, an appropriate and rapid decrease in CO2 gas emission levels has become a significant challenge. Capturing CO2 on a solid surface is proposed due to its ease of application, relatively low energy requirements, and applicability in various processes. This study investigated the preparation of Xerogel@MgAl LDH (X@MAL) composite for CO2 capture. Firstly, silica-based xerogel was synthesized by the acid and base-catalyzed two-step sol-gel method. Then, the X@MAL composite was prepared by the co-precipitation method. Based on the CO2 capture analysis, the maximum CO2 capture capacity of the composite at 25 degrees C, 75 degrees C, and 100 degrees C was 1.90 mmol.g(-1,) 0.70 mmol.g(-1), and 0.40 mmol.g(-1), respectively. The kinetic analysis results show that the CO2 capture of X@MAL can be well-defined by Avrami kinetic model.
Keywords: CO2 Capture; Kinetics; Layered Double Hydroxide; Xerogel; MESOPOROUS SILICA; ADSORPTION; SORPTION; AEROGEL; DYE; Engineering